Ultrasound-guided in vivo histotripsy in rabbit kidneys using millisecond-length two-stage ultrasound pulses combined with fundamental and second harmonic superposition. (7th November 2022) - Qi, Tingting; Yang, Rongzheng; Liu, Xuan; Lu, Mingzhu; Liu, Yehui; Li, Ruixin; Mao, Jianyun; Zhang, Yi; Jing, Yanshu; Chang, Juntao; Zhang, Quan; Wan, Mingxi
Abstract: Objective. Histotripsy is a non-invasive focused ultrasound ablation method that can mechanically disintegrate tissues. This study aims to verify that ultrasound-guided histotripsy using millisecond-length two-stage ultrasound pulses combined with fundamental and second harmonic superposition can enhance treatment in rabbit kidneys in vivo. Approach. Rabbit kidneys ( n  = 10) were treated using a custom-designed 1.1/2.2 MHz two-element confocal-annular array, with lateral and axial full width at half-maximum pressure dimensions of approximately 1.0 and 6.0 mm. Two-stage ultrasound pulses were applied: stage 1 used 60–80 pulses with a pulse duration of 6 ms and a pulse repetition frequency of 10 Hz. Meanwhile, stage 2 consists of 2–4 periods, each period consists of a concentrated pulse train of localized high DC of 6% and an off-time of 3–5 s, with an average DC of 1%–1.5%. B-mode ultrasound imaging was used to guide and monitor the boiling and cavitation bubbles. Main results. Ultrasound-guided treatment was successful in all rabbits, and the ablation rate is about seven times that of single-frequency combined two-stage pulses, achieving enhanced histotripsy. The regular elliptical lesions with dimensions of 10.6 ± 0.8 mm × 3.9 ± 0.6 mm (axial × lateral) were generated, and a large-volume lesion was generated by multi-point treatment. The size of most lysates was about 2.5 μ m. Histologically, lesions were completely homogenized and well demarcated between treated-untreated areas. There was no apparent damage to critical structures surrounding lesions. Nonlinear simulations revealed that it may be the interaction between shock front and the cavitation and boiling bubbles generated by the dual-frequency effect enhanced the treatment efficiency. Significance. The novel histotripsy could improve treatment efficiency and generate regular elliptical lesions with controllable shape and axial dimensions, which may be a useful tool in treating renal cell carcinoma.